2016
DOI: 10.1177/0954405416662082
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric flow observation at inter-electrode gap in micro-electro-discharge-milling process

Abstract: The material removal phenomenon of sparking and melting in micro-electro-discharge-milling process occurs at interelectrode gap of dimension less than 50 mm. The behavior of fluid flow properties at inter-electrode gap is not well discussed in the literature and its information will be useful to understand the material flow behavior and tool wear in micro-electro-discharge-milling process. Based on our previous findings, it was well recognized that tool rotation is an inherent part of micro-electro-discharge-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…As the variation in velocity is less even with the small gap width, the flushing will be effective. When compared with the ADV in the IEG using cylindrical tool, 25 the velocity in case of slotted tool is less for dissimilar gap width. The reason is vortex flow in the slot which reduces the velocity.…”
Section: Resultsmentioning
confidence: 99%
“…As the variation in velocity is less even with the small gap width, the flushing will be effective. When compared with the ADV in the IEG using cylindrical tool, 25 the velocity in case of slotted tool is less for dissimilar gap width. The reason is vortex flow in the slot which reduces the velocity.…”
Section: Resultsmentioning
confidence: 99%
“…It was determined that many bubbles were generated during the discharge process, most of which were connected during discharge before expanding rapidly and pushing most etched particles to the edge of the bottom gap. Mullya and Karthikeyan 16 analyzed the fluid flow along the narrow gap of micro-electro-discharge-milling process for different machining conditions by computational fluid dynamics simulation, and the effect of different sized particles formed at various positions and their subsequent movement was also analyzed by particle simulation. The results showed that the average velocity of the fluid in the gap was affected by the change in the inlet nozzle velocity, and the eddies were created due to the change fluid pattern.…”
Section: Introductionmentioning
confidence: 99%